2021
DOI: 10.31234/osf.io/ahqwj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What is time good for in working memory?

Abstract: Increasing time to process information in working memory (WM) improves performance. Free time given after an item is often assumed to enable maintenance processes to counteract forgetting of this item, suggesting that time has a retroactive benefit. Two other hypotheses – short-term consolidation, and temporal distinctiveness – entail a local effect of time on immediately preceding and following items. Here, we show instead a novel, global and proactive, benefit of time in WM. In three serial-recall experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…These results are consistent with a similar recent finding in a working memory serial recall task (Mizrak & Oberauer, 2021). Mizrak and Oberauer found that if one of the intervals in a list of seven words is longer (2500ms) rather than shorter (500ms), this leads to better memory for all subsequent items, but not for the preceding items.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are consistent with a similar recent finding in a working memory serial recall task (Mizrak & Oberauer, 2021). Mizrak and Oberauer found that if one of the intervals in a list of seven words is longer (2500ms) rather than shorter (500ms), this leads to better memory for all subsequent items, but not for the preceding items.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the seemingly unlimited capacity of long-term memory (LTM;Brady et al, 2008;Konkle et al, 2010;Standing, 1973), there is a limit on how much information can be added to LTM at any given time. As an example of this limit, consider that both short-term memory (STM) and LTM performance consistently degrades when the "free time" between study items is reduced (Brown et al, 2006;Criss & McClelland, 2006;Malmberg & Nelson, 2003;Mizrak & Oberauer, 2021;Ricker & Hardman, 2017). This limitation could arise through various mechanisms -it could be due to reduced temporal distinctiveness (Brown et al, 2006), due to reduced opportunity for articulatory rehearsal or attentional refreshing (Camos et al, 2009), or due to the interruption of a consolidation process (Ricker & Hardman, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This way of encoding items naturally creates a primacy gradient whose existence is empirically supported (Oberauer, 2003). The plausibility of the encoding-resource account has recently received support from fine-grained investigations of the beneficial effect of free time in immediate serial recall tasks (Mizrak & Oberauer, 2021). Critically, this model can explain the presence of proactive effects in WM.…”
Section: The Encoding-resource Hypothesismentioning
confidence: 94%
“…In delayed free recall tasks in which no words are semantically associated, recall performance decreases over serial position (Murdock, 1962). This decrease in probability of recall may arise from decreases in attention (Sederberg et al, 2006; Azizan & Polich, 2007), and/or a decline in encoding resources (Lohnas et al, 2020; Popov & Reder, 2020; Mizrak & Oberauer, 2021). Consistent with previous research, we find a decrease in probability of recall for late list items that did not semantically overlap with a prior list item.…”
Section: Discussionmentioning
confidence: 99%